2007
DOI: 10.1104/pp.107.107912
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in Nicotianamine Aminotransferase Stimulated the Fe(II) Acquisition System and Led to Iron Accumulation in Rice

Abstract: Higher plants acquire iron (Fe) from the rhizosphere through two strategies. Strategy II, employed by graminaceous plants, involves secretion of phytosiderophores (e.g. deoxymugineic acid in rice [Oryza sativa]) by roots to solubilize Fe(III) in soil. In addition to taking up Fe in the form of Fe(III)-phytosiderophore, rice also possesses the strategy I-like system that may absorb Fe(II) directly. Through mutant screening, we isolated a rice mutant that could not grow with Fe(III)-citrate as the sole Fe source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
165
1
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(181 citation statements)
references
References 46 publications
(50 reference statements)
6
165
1
6
Order By: Relevance
“…It was concluded that Zn is highly mobile in phloem Rengel 1994, 1995;Haslett et al 2001). Similarly, the transport of iron in phloem is well studied although the transport mechanism is not well known and may involve citric acid conjugates and/or nicotianamine as a transport system with most of the studies on Fe-transport based on mutants in peas (Grusak 2000(Grusak , 2002 or Arabidopsis (Grotz and Guerinot 2006), or rice (Takahashi et al 2001;Cheng et al 2007;Masuda et al 2009). Iron-uptake through iron reductase activity (IRA) seems to be important for total seed accumulation of this mineral in common bean (Blair et al 2010a).…”
Section: Iron and Zinc Uptake Accumulation And Translocation To mentioning
confidence: 99%
See 2 more Smart Citations
“…It was concluded that Zn is highly mobile in phloem Rengel 1994, 1995;Haslett et al 2001). Similarly, the transport of iron in phloem is well studied although the transport mechanism is not well known and may involve citric acid conjugates and/or nicotianamine as a transport system with most of the studies on Fe-transport based on mutants in peas (Grusak 2000(Grusak , 2002 or Arabidopsis (Grotz and Guerinot 2006), or rice (Takahashi et al 2001;Cheng et al 2007;Masuda et al 2009). Iron-uptake through iron reductase activity (IRA) seems to be important for total seed accumulation of this mineral in common bean (Blair et al 2010a).…”
Section: Iron and Zinc Uptake Accumulation And Translocation To mentioning
confidence: 99%
“…Rice is an exception in the sense that it possesses both systems for Fe uptake, making it especially Fe efficient (Cheng et al 2007). Plant roots and their exudates greatly facilitate the availability of various plant nutrients by bringing them in the soluble form in the soil (Neumann and R€ omheld 2002;Rengel 2002;Ryan and Graham 2002;Welch and Graham 2004).…”
Section: Plant Traits Associated With Increased Acquisition Of Iromentioning
confidence: 99%
See 1 more Smart Citation
“…This increased NA also enables plants to tolerate toxic concentrations of nickel (11,14). Disruption of the rice nicotianamine aminotransferase (NAAT1) enzyme, which uses NA as the substrate, results in a significant elevation of Fe concentrations in both seedlings (by 15.8% in shoots and 41.8% in roots) and seeds (1.8-fold) (15). Among the 3 OsNAS genes present in rice, OsNAS1 and OsNAS2 transcripts are markedly elevated in both roots and leaves in response to Fe deficiency, whereas OsNAS3 expression is induced in roots but suppressed in leaves when the Fe supply is inadequate (16).…”
mentioning
confidence: 99%
“…Under low-iron conditions, grasses such as rice (Oryza sativa) and maize (Zea mays) primarily utilize the Strategy II response, whereby they release phytosiderophores into the rhizosphere that bind to ferric iron with high affinity. Phytosiderophore-ferric iron complexes are transported into the root via membrane-localized yellow stripe and yellow stripe-like (YSL) transporters (Curie et al, 2001;Inoue et al, 2009), although several studies suggest that rice is also able to directly uptake ferrous iron (Ishimaru et al, 2006;Cheng et al, 2007).…”
mentioning
confidence: 99%